Pengaruh Lingkungan Kerja dan Beban Kerja terhadap Kepuasan Kerja Karyawan Wisma Sehati BSD Tangerang Selatan - May Nena Ray Dalena; Syarif Ali; Ediwarman Ediwarman (Studi Ilmu Manajemen dan Organisasi, 2020)
Purpose: This research is a research using a quantitative approach which aims to find out and prove the effect of the work environment and workload on the job satisfaction of the employees of Wisma Sehati BSD Tangerang Selatan branch. Research methodology: The population in this research were 30 employees and the sample used in this research was the same number of 30 people using the saturated sample technique. In collecting data, the data was distributed using an online questionnaire via Google Form. The analytical tool used in this research is SmartPLS 3.3.3 with the analysis technique used is path analysis. Limitations: (1) Limitations in the use of this measurement variable may not fully indicate the causes that also affect employee job satisfaction. (2) In addition, this research is only distributed to employees in one company. (3) And this research took place during the covid-19 pandemic so that it experienced limitations in distributing questionnaires Contribution: (1) This research is expected Wisma Sehati BSD to maintain and improve employee satisfaction by continuously maintaining and improving the quality of a good and comfortable work environment and improving a balanced workload. (2) Expected to be able to explore and implement the insights and knowledge that has been obtained during lectures regarding Human Resource Management that has been obtained while studying at the Management Study Program S1. (3) And also add insight which can then be applied in the management of human resources in the future